Validity and reliability of an observational instrument to describe practices in pharmacodelivery in a public tertiary hospital - Hipolito, Melissa Jean G.; Espallardo, Myza C.; Feliciano, Toni Anne O.; Genuino, Karissa Arielle F.; Magalong, John Vincent U.; Travilla, Faye S.
While there are existing instruments on medication safety, no standard instrument has been developed to describe local practices in pharmacodelivery. With this need, the study used a mixed method instrument design to develop a valid and reliable instrument which describes practices in pharmacodelivery in a tertiary hospital in the Philippines. Items for a semi-structured observational instrument were generated from literature and were used to collect field observations. The instrument was then revised based on the field observations and was thereafter evaluated for readability and ability to be understood through pretesting, face and content validity with a panel of six experts, and inter-observer reliability. Evaluation yielded an overall content validity index of .91. Subjective judgments of the experts were considered in the revision of the tool. Inter-observer reliability ranged from rs = .89 to .92 (p <.01) while percentage agreement values ranged from 92% to 100% showing good reliability for both measures. The 151- item observation instrument developed is shown to be a reliable and valid tool for describing practices in pharmacodelivery of a tertiary hospital in the Philippines. The findings invite further investigations on the practices in pharmacodelivery in the local setting.